Consumption-Savings Trade-Off in the Allocation of Migrants; Remittances and Economic Growth: The Cases of Burkina Faso and Senegal (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: remittances; consumption; savings; investment; economic growth; CGE model